+0  
 
+5
131
2
avatar+98 

Evaluate the expression $$\int^3_{-2}x^2-2x+3 dx$$

 Feb 14, 2021
 #1
avatar+120129 
+2

                             3

x^3/3  - x^2   + 3x  ]           =

                             -2

 

[ 3^3/3   - (3)^2  + 3(3)  ] -  ( -2)^3/3  - (-2)^2  + 3(-2)  ] =

 

[ 9   - 9 +  9 ]  - [ -8/3  - 4  - 6  ] =

 

9 + 8/3 + 4  + 6   =

 

65/3

 

 

cool cool cool

 Feb 14, 2021
 #2
avatar+266 
+5

\(\int _{-2}^3x^2-2x+3dx\)

 

\(=\int _{-2}^3x^2dx-\int _{-2}^32xdx+\int _{-2}^33dx\)

 

\(=\frac{35}{3}-5+15\)

 

\(=\frac{65}{3}\)

 

cheekycheekycheeky

.
 Feb 14, 2021

20 Online Users

avatar
avatar
avatar
avatar